Pengaruh Kompres Hangan Jahe Merah terhadap Skala Nyeri Lansia Osteoarthritis di Balai Sosial Lanjut Usia Mandalika Mataram - Istianah, Istianah; Lestari, Windi Kurnia; Hapipah, Hapipah; Supriyadi, Supriyadi; Hidayati, Nurul; Rusiana, Harlina Putri (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2020)
Osteoarthritis is a disorder deseaseof the joint that cause the decrease of join motion. Pain is amajor problem in osteoarthritis patients, so the management of this disease focuses on efforts to resolve or recover from the pain. Giving a red ginger compress is an alternative to reduce joint pain in elderly who suspect of osteoarthritis. This research was conducted at BalaiSoaialLanjutUsia( BSLU )MandalikaMataram. The research design used in this research was experimental observational with one group pretest-posttest. The sampling technique used purposive sampling with a sample quantity of 14 respondents and the data collection tool in this study was the observation sheet.Data were analyzed by univariate and bivariate. The Wilcoxon test results obtained a value of 0.001 (p value <0.05). It can be concluded that the warm red ginger compress has an effect on reducing the pain scale in the elderly with osteoarthritis. It is hoped that the results of this study can be disseminated by providing counseling to the community where warm red ginger compresses can be used as a non-pharmacological technique to reduce pain in elderly people with osteoarthritis so that it can improve health services